Paradigmas alternativos de computación: paralelismo y simplicidad inspirados en la biología - Rojas Galeano, Sergio Andrés (Ingeniería, 1999)
While sequential computers have achieved astonishing progress in our recent history, it can't demonstrate successful application in complex problems where autonomous, robustness and efficient machines are required to operate in a threatening and dynamic environment. There are another alternative computing models that become as cellular computing, motivated primary in biologics. And certainly, they had shown good promises. This paper is a reviewing of this issue, its features and some advances.